Teaching and learning in bilingual classrooms : new scholarship - Mulrooney, Kristin J. (Sociolinguistics in deaf communities series ;, 2014)
A new initiative known as the Scholarship of Teaching and Learning (SoTL) strives to improve education today by methodically examining and assessing the vital component of classroom interaction. This collection presents research by five professors who adopted SoTL methodology to study their own classrooms at Gallaudet University, a uniquely diverse bilingual institution that employs both American Sign Language (ASL) and written English. The Gallaudet study, called the GSTLI, intended to create an engaged learning community that investigated, reflected upon, and documented strategies that most effectively enhance learning for linguistically diverse, visually oriented populations. After extensive SoTL training, the GSTLI professors reviewed interaction in their respective classrooms. Through meticulous study of class videos and written assignments in three General Studies Requirements courses for first-year students, the teachers learned how to ensure connecting with students who have a variety of language differences and communication methods. The other professors assessed bottlenecks in classes on the linguistic structure of ASL, and on criminal justice. The linguistics professor identified the bottleneck as the students' inability to conceptualize the interrelationship between definitions and examples, a fundamental skill to scientific thinking. In the criminal justice class, the professor saw the need to guide students through linguistic bottlenecks by providing materials in both ASL and English. The successes of the GSTLI presented in this unique volume can benefit other teachers by better preparing them to meet the needs of bilingual diverse learners in more effective ways.